Gender Representation in Nepalese Secondary Level English Textbooks: A Multimodal Analysis (Interdisciplinary Research in Education, 2024)
English has been playing a central role in Nepalese school education for centuries, serving both as a subject and a medium of instruction. As mandatory at-hand materials in teaching and learning processes, textbooks play a vital role in achieving curriculum objectives and influence students’ cognitive development and gender awareness. In Nepal, where gender stereotypical norms persist, it is crucial to maintain gender balance in educational materials for fostering equity.  Although equitable quality education for all is the agenda for sustainable development goals and feminist scholars' advocacy for gender-neutral language and imagery, the National Curriculum Framework (NCF) 2019 does not explicitly address gender balance in ELT curricula, policy implementation or in textbooks. This study analyzes gender biases and stereotypical representations in the Grade-10 compulsory English textbook used in Nepalese schools.Using a multimodal technique, the study analyses authorships, layout, visual images, reading texts, and exercises to uncover gender representation. The findings disclose persistent underrepresentation and biased gender role representations of female characters, and a lack of gender-inclusive activities in the textbook. The study highlights the need for revising the newly implemented secondary level compulsory English textbooks to promote gender-sensitive and gender inclusive learning environments, collaborating among key stakeholders.